Coronavirus disease 2019 associated mucormycosis meandering its way into the orbit: a pictorial review. Issue 11 (15th November 2021) - Khullar, T; Kumar, J; Sindhu, D; Garg, A; Meher, R; Goel, R
Abstract: Background: There has been a recent deluge of coronavirus disease 2019 associated mucormycosis in our country. It affects the paranasal sinuses; however, it has a rapid extrasinus progression (the orbit being most common), which can be fatal if not detected early. It may meander into the orbit through various foramina without frank bone destruction. Methods: This paper reviews the various gateways of the spread of coronavirus disease 2019 associated mucormycosis to the orbit, even before advent of bone destruction or ocular symptoms. Plausible pathways of invasion and subtle imaging findings are depicted, to enable an early diagnosis. Results: Relevant anatomy and imaging examples have been illustrated to familiarise the surgeons with various routes of coronavirus disease 2019 associated mucormycosis spread to the orbit. Emphasis is laid on searching for subtle imaging findings for the detection of early orbital invasion. Conclusion: Early detection and extension of coronavirus disease 2019 associated mucormycosis is facilitated by knowledge of its gateways of spread, which aids the surgeon in prognostication and planning of the surgical approach.